2016
DOI: 10.1136/injuryprev-2016-042023
|View full text |Cite
|
Sign up to set email alerts
|

Perils of police action: a cautionary tale from US data sets

Abstract: ObjectiveTo count and characterise injuries resulting from legal intervention by US law enforcement personnel and injury ratios per 10 000 arrests or police stops, thus expanding discussion of excessive force by police beyond fatalities.DesignEcological.PopulationThose injured during US legal police intervention as recorded in 2012 Vital Statistics mortality census, 2012 Healthcare Cost and Utilization Project nationwide inpatient and emergency department samples, and two 2015 newspaper censuses of deaths.Expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 21 publications
2
62
0
Order By: Relevance
“…Deaths due to police violence are undercounted in official vital statistics and crime records 2. However, previous epidemiological studies have found that systematically compiled news accounts are a reliable source of injury data 2 6.…”
Section: Methodsmentioning
confidence: 99%
“…Deaths due to police violence are undercounted in official vital statistics and crime records 2. However, previous epidemiological studies have found that systematically compiled news accounts are a reliable source of injury data 2 6.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] Still, others have produced analyses of existing injury and mortality data derived from hospital records and death certificates. [9][10][11] Researchers have yet to answer basic epidemiological questions about police violence, however, such as whether the incidence rate of injuries caused by US police has changed over time, or the degree to which these injuries are properly coded as Blegal intervention^(i.e., those caused by law enforcement, as per the International Classification of Diseases (ICD)) and are therefore identifiable in statistical analyses of hospital data. Additionally, little attention has been paid to the role of private security guards in use-of-force incidents, even as the private security industry has grown steadily since 2001, and the number of private guards in the USA has come to be roughly equal to the number of police officers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to job loss after incarceration, survivors of brutality may have to deal with disabilities resulting from police use of excessive force. 11 Disability decreases productivity and the ability to accumulate financial resources.…”
Section: Economic and Financial Strainmentioning
confidence: 99%
“…10 Police killings increase Black-specific mortality rates. Even though only two percent of injuries from police interventions that require treatment in the emergency department or hospital result in death, 11 Blacks are almost five times more likely than are Whites to have a police intervention-related injury. 12 Little is known about the prevalence of nonlethal police violence that results in injury or disability.…”
mentioning
confidence: 99%